Hospital Size and Cybersecurity Practices: Evaluating Nurses' Awareness in Indonesia - Irwandy Irwandy; Adelia U. Ady Mangilep; Rini Anggraeni; Noer Bahry Noor; Andi Niartiningsih; Nur Latifah; Andi Azisah Bari’ah (Journal of Public Health and Pharmacy, 2025)
Introduction: This study aimed to evaluate nurses' knowledge, attitudes, and practices (KAP) regarding cybersecurity in healthcare settings, focusing on variations across hospitals of different sizes. Cybersecurity is critical in the digitalization of healthcare, yet gaps in awareness and training persist, particularly in developing countries. With increasing cyber threats targeting healthcare institutions globally, this study seeks to address the underexplored role of nurses in safeguarding hospital information systems. Methods: This cross-sectional study was conducted in three government hospitals in Makassar, Indonesia, from [start month/year] to [end month/year]. A total of 331 nurses participated, representing hospitals of varying organizational sizes and bed capacities. Data were collected using structured questionnaires, assessing KAP related to cybersecurity. Ethical approval was obtained from [name of ethics committee], and written informed consent was secured from all participants. Data were analysed using descriptive and inferential statistics, with significance set at p < 0.05. Results: The study revealed significant gaps in nurses' cybersecurity knowledge, attitudes, and practices. Awareness of hospital cybersecurity policies was low (43.2%), particularly in larger hospitals. Hospital 3, the smallest, exhibited higher awareness (59.0%) compared to Hospital 1 (35.8%) and Hospital 2 (39.6%) (p = 0.03). Risky behaviours, such as using personal devices for sensitive data transfer, were prevalent (77.0%), with the highest incidence in larger hospitals. Statistical analyses confirmed significant variations in cybersecurity KAP based on hospital size and organizational complexity. Conclusion: This study highlights the critical need for targeted cybersecurity training programs, particularly for nursing staff in larger hospitals, through raising awareness of social engineering attacks, email scams, and infection detection. By addressing gaps in awareness and practices, hospitals can enhance data protection and mitigate risks. Future research should explore tailored interventions and organizational factors influencing cybersecurity in healthcare systems to inform global health policies.